Perencanaan Kawasan Wisata Pantai Pudak Berbasis Komunitas : (Perencanaan Kawasan Wisata Pantai Pudak Berbasis Komunitas) - Darmawan, Daffine; Cahyono, Hendry (Universitas Negeri Surabaya, 2025)
Abstract One of the most significant macroeconomic factors is the exchange rate as its changes have the Pudak Beach has great potential as a marine tourism destination; however, its development still faces various challenges, such as a lack of supporting infrastructure and low community involvement in its management. This study aims to design a tourism area plan for Pudak Beach using a community-based approach to improve the local community’s economic well-being while preserving environmental sustainability. The research method used is a qualitative descriptive approach with data collection techniques including observation, in-depth interviews, and discussion forums with the community and other stakeholders. The results show that active community involvement in the planning and management of tourism can enhance tourist appeal, create job opportunities, and strengthen local cultural identity. Therefore, a development strategy that prioritizes community participation, environmental conservation, and human resource capacity building is essential.